Synthesis of Spiro Heterobicyclic Rings Using Cellulose Sulfuric Acid Under Solvent Free Conditions - Montazeri, Naser; Pourshamsian, Khalil; Bayazi, Masoud; Kabiri, Soudabeh (Asian Journal of Chemistry, 2013)
Cellulose sulfuric acid is found to be a heterogenic recyclable catalyst for the rapid and efficient synthesis spiro heterobicyclic rings via a three component condensation reaction between aldehydes, barbituric acid and urea (or thiourea) under solvent-free conditions. The method offers several advantages, including high yields, short reaction times, simple work-up procedure and reusability of the catalyst. We believe that this applicability of cellulose sulfuric acid with mention advantages makes our method superior over all reported methods to the synthesis of spiro heterobicyclic compounds.